Pengaruh Penerapan Media Pembelajaran Anagram Wordwall Terhadap Kemampuan Membaca Al-Qur’an Siswa Kelas VI SD Negeri 9 Telaga Biru - Dwy Putri Cahyati; Abd. Hamid Isa; Yulanti S. Mooduto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of Anagram Wordwalls Learning Media on the Quranic Skills of sixth-Grade Students at SD Negeri 9 Telaga Biru. The research method used in this study was a quantitative quasi-eksperimental design with a nonequivalent Control Grup Design. The number of subject was 33 sixth-grade studen at SD Negeri 9 Telaga Biru. Data collection techniques included observation, Pretest, posttest, and documentation. The result of the non-parametric tes showed a significant difference between the result of the improvement in Quranic reading skills of the expeimental and control classes. Therefore, the aplication of an Anagram Wordwalls learning media can influence the Quranic reading skills of sixth-grade students at SD Negeri 9 Telaga Biru. It is recommended that scool provide facilities and training for educators, particularly regarding the ability to use digital learning.